2021
DOI: 10.1038/s41598-021-98904-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intestinal viability by consecutive photoacoustic monitoring of oxygenation recovery after reperfusion in acute mesenteric ischemia in rats

Abstract: The purpose was to assess whether consecutive monitoring of oxygenation by photoacoustic imaging (PAI) can objectively predict intestinal viability during surgery for acute mesenteric ischemia (AMI). PAI uses laser light to detect relative amounts of oxygenated and deoxygenated hemoglobin in intestinal tissue. In 30 rats, AMI was induced by clamping the mesenteric and marginal vessels of the ileum for 0 min in the control group, 30 min in the mild group, and 180 min in the severe group (10 rats per group). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In particular, PAI as a non-invasive optical imaging technique is based on near infrared optical absorption of two major components of in vivo biological tissues, i.e., oxyhemoglobin (HbO 2 ) and deoxyhemoglobin (HbR), which can enable quantification of blood oxygen saturation (sO 2 ) in tissues [19] , [20] . For example, Sugiura et al demonstrated that PAI has the capability for consecutive monitoring of oxygenation recovery after reperfusion in acute mesenteric ischemia in rats [21] . In addition, Hallasch et al revealed that PAI was able to detect the early-stage psoriatic arthritis [22] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PAI as a non-invasive optical imaging technique is based on near infrared optical absorption of two major components of in vivo biological tissues, i.e., oxyhemoglobin (HbO 2 ) and deoxyhemoglobin (HbR), which can enable quantification of blood oxygen saturation (sO 2 ) in tissues [19] , [20] . For example, Sugiura et al demonstrated that PAI has the capability for consecutive monitoring of oxygenation recovery after reperfusion in acute mesenteric ischemia in rats [21] . In addition, Hallasch et al revealed that PAI was able to detect the early-stage psoriatic arthritis [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Various ways have been proposed for the viability assessment [6][7][8][9][10][11][12][13][14][15]. Most of these ways determine the state of blood circulation in the vessels of bowel walls.…”
Section: Introductionmentioning
confidence: 99%
“…But this way is subjective and not reliable enough [5,6]. There are many ways to objectively assessment [6][7][8][9][10][11][12][13][14][15][16]. Most of them determine the intensity of blood circulation in bowel wall tissues [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%